Sustainable C(sp3)-H Bond Functionalization - Xie, Jin.; Zhu, Chengjian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book highlights major achievements made in the last five years concerning sustainable C(sp3)-H bond functionalization and offers a promising and emerging tool-kit for organic synthesis. The book is divided into three chapters demonstrating key advances in C(sp3)-H bond functionalization. Chapter 1 reviews transition-metal-catalyzed C(sp3)-H bond functionalization using different directing groups, while Chapter 2 addresses the new methods of transition-metal-catalyzed and metal-free C(sp3)-H bond functionalization without directing groups, in addition to briefly highlighting redox-neutral C(sp3)-H bond functionalization. In closing, Chapter 3 examines visible-light photoredox catalysis, an emerging and highly sustainable C(sp3)-H bond functionalization strategy. The book offers an intriguing and useful reference guide for a broad readership working and/or interested in the fields of organic, organometallic, and greenchemistry.
Transition-Metal-Catalyzed, Directing Group Assisted C(sp3)-H Bond Functionalization -- Recent Advances in Non-Directed C(sp3)-H Bond Functionalization -- Functionalization of C(sp3)-H Bond by Visible-Light Photoredox Catalysis.
Keywords: Organometallic chemistry .; Catalysis; Chemistry, Technical; Organometallic Chemistry; Catalysis; Industrial Chemistry